2011
DOI: 10.1097/iae.0b013e3181eac724
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Anesthetic Methods for Intravitreal Injections

Abstract: Topical anesthesia is an effective method for limiting pain associated with intravitreal injections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 11 publications
4
43
3
2
Order By: Relevance
“…A similar study conducted by Blaha et al prospectively compared the effectiveness of 0.5% proparacaine, 0.5% tetracaine, 4% lidocaine pledget, and subconjunctival injection of 2% lidocaine for intravitreal injection in 24 patients. There was no statistical difference in pain control among the different anesthetic options although subconjunctival lidocaine injection had the most side effects (subconjunctival hemorrhage and the possibility of intravitreal injection of lidocaine) [9]. These results were consistent with the findings of similar study performed by Kozak in 2005 in which it was showed that lidocaine 2% gel provided satisfactory pain control and produced less chemosis and hemorrhage than subconjunctival anesthesia [10].…”
Section: Articlesupporting
confidence: 82%
“…A similar study conducted by Blaha et al prospectively compared the effectiveness of 0.5% proparacaine, 0.5% tetracaine, 4% lidocaine pledget, and subconjunctival injection of 2% lidocaine for intravitreal injection in 24 patients. There was no statistical difference in pain control among the different anesthetic options although subconjunctival lidocaine injection had the most side effects (subconjunctival hemorrhage and the possibility of intravitreal injection of lidocaine) [9]. These results were consistent with the findings of similar study performed by Kozak in 2005 in which it was showed that lidocaine 2% gel provided satisfactory pain control and produced less chemosis and hemorrhage than subconjunctival anesthesia [10].…”
Section: Articlesupporting
confidence: 82%
“…In agreement with this conclusion, Yau et al, showed that there was no difference in patient pain experience between the 3 (tetracaine, lidocaine and cocaine) anesthetic options tested [7]. Similarly, Blaha et al, compared lidocaine pledget, topical proparacaine, subconjunctival lidocaine and topical tetracaine without obtaining any significant difference in patient pain experience [8].…”
Section: Discussionsupporting
confidence: 59%
“…First, the similarity in pain may reflect the use of the same topical anesthesia protocol in both groups. Topical anesthesia with lignocaine gel is very effective for intravitreal injections, [30][31][32][33][34] and it may have blunted the increased pain that could have resulted from the larger Ozurdex injection. Second, Ozurdex was injected through a customized applicator, whereas bevacizumab was injected from a simple syringe.…”
Section: Discussionmentioning
confidence: 99%
“…Although no consensus has been reached, topical anesthesia by either drops or gel has been repeatedly shown to be very effective in pain control during intravitreal injections. [26][27][28][30][31][32][33] Therefore, it has been generally agreed that topical anesthesia is most comfortable and cost effective, 27,32,34 and this is currently the most commonly used protocol before intravitreal injections. Pain associated with intravitreal injections is generally mild, and mean VAS scores reported in previous studies during these injections varied from 12 to 35.…”
Section: Discussionmentioning
confidence: 99%